Learning to Write "Good": A Recipe for Teaching the Recalcitrant Writer - La Rae M. Donnellan (Journal of Applied Communications, 1982)
Changing attitudes about writing through a fast-paced presentation of pertinent information, laced with a healthy dash of humor.